MOTIVATIONAL MECHANISM OF THE ANIMAL HUSBANDRY REVIVAL AND DEVELOPMENT - Лаврук, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
It is pointed out that the motivational mechanism serves as a conceptual basis to motivate workers to productive employment for the purpose of animal husbandry revival and development. In its environment a major element of motivational decision is the choice of motivation strategies and methods of its implementation within the current management system of animal husbandry labor collectives. The aim of the study is scientific and theoretical substantiation of motivational mechanism formation expediency and its use in the process of rebirth and effective development of animal husbandry. The methodological basis for this mechanism formation is the system and abstract-logical approaches use taking into account the characteristics and functioning of the labor market; economic; organizational; social and other factors that affect the motivational level of the animal husbandry employees. The motivational mechanism design was grounded characterized by the combination of forms; types; methods of motivation and employees work organization by determination of quantitative parameters of each element. It was found that motivational mechanism makes the main participants of the production process in cattle breeding to increase the productivity of labor; takes into account the personal individual needs and interests of livestock producers; whose wants may be satisfied in the process of their labor activity. It was proposed the motivational mechanism model that will increase the management efficiency of livestock enterprises socio-economic activities; as it targeted on the rational use of production resources; increasing the workers productivity; the volumes of competitive livestock production and profitability of livestock industries.